2017
DOI: 10.1002/hed.25019
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of returns to the emergency department after head and neck surgery

Abstract: The rate of 30dEDRs after head and neck surgery is low; however, these visits increase the hospitals' financial burden as well as patient morbidity. Predictors of 30dEDRs may be utilized to formulate preventative measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
(94 reference statements)
2
11
0
Order By: Relevance
“…31-34 Although not well studied, the rate of return ER visits after head and neck surgery has been reported as being 7.5%. 35 A conservative estimate of otolaryngologic surgeries performed per year is about 6 million, 36 which would suggest there are about 450,000 post-operative ER visits a year, of which about 60% are sent home. 35 It is thus imperative that effective methods are developed to reduce unnecessary unplanned ER visits.…”
Section: Discussionmentioning
confidence: 99%
“…31-34 Although not well studied, the rate of return ER visits after head and neck surgery has been reported as being 7.5%. 35 A conservative estimate of otolaryngologic surgeries performed per year is about 6 million, 36 which would suggest there are about 450,000 post-operative ER visits a year, of which about 60% are sent home. 35 It is thus imperative that effective methods are developed to reduce unnecessary unplanned ER visits.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Prior studies performed in North American otorhinolaryngology -head and neck surgery departments seeking to identify risk factors for unplanned hospital readmission among patients undergoing otolaryngology procedures reported rates of hospital readmission ranging from 3.1 to 7.3%. 2,[4][5][6][7][8][9] These studies identified a strong association between the occurrence of postoperative complications and unplanned 30-day readmissions. 2,10 In another study that included 1,058 patients undergoing ear, nose, and throat (ENT) surgery, Graboyes et al found that patients who experienced a complication during or after their index hospitalization were 11.9 times more likely to be readmitted to the hospital within 30 days than patients without complications.…”
Section: Introductionmentioning
confidence: 99%
“…2 Regarding the reported 30-day readmission rates for head and neck surgery, it ranges from 3.2 to 26.5%, depending on the subsite, on the complexity of the surgery, and on a variety of factors. 2,3,[7][8][9]11,12 There is no data reported from European otorhinolaryngology -head and neck surgery departments about unplanned hospital readmission after head and neck surgery. Moreover, further understanding is needed about the risk factors associated with this.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations